Pelatihan Pemasaran Digital Sebagai Bekal Wirausaha Muda Siswa SMK Muhammadiyah 6 Karanganyar - Hadi Utomo, Fahman; Karin Rizkiawan, Ilham; Uswatun Khasanah, Aulia; Syifa Salsabila, Najla (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
This community service activity aims to equip students of SMK Muhammadiyah 6 Karanganyar with basic skills in digital marketing as part of their preparation to become young entrepreneurs in the digital era. This training is motivated by the need for digital literacy and technology-based marketing skills which are the key to success in running an independent business today. Social media, one of the rapidly growing and highly potential information technologies, offers many benefits for users, including increased productivity and marketing capabilities. The training is provided in the form of interactive workshops, direct practice of creating promotional content, and simulations of using social media (Instagram, WhatsApp Business, TikTok) and marketplace platforms (Shopee, Tokopedia) for product marketing. The solution of the community service activity in organizing Digital Marketing Training as a Provision for Young Entrepreneurs Students of SMK Muhammadiyah 6 Karanganyar so that they can increase product sales by participating in digital marketing training. Our hope from this training is to be able to keep up with developments in the digitalization era, so that they can market products more practically and efficiently. Providing mentoring in the implementation of digital marketing strategies.The output of this community service program is that students at Muhammadiyah 6 Karanganyar Vocational School are equipped to enter the business world directly. Students' awareness of the importance of digital marketing in increasing sales and scientific publications in ISSN journals is also increased.